Technology advances in contraception. - Riitta Fuchs, Anna (2015)
It is completely unnecessary to emphasize the need for contraception in a world in which every year eighty million individuals are added. In just 25 years the world population will double its current size. In many parts of the world food shortages and other natural resources it is already becoming evident, in others, the consequences of the growth rates of the population feel mainly in the deterioration of the environment. Everywhere in the world the pressures of ever-growing populations and more young people are able to create social and political disorder and violence.